2016
DOI: 10.1155/2016/3582176
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Scintillation Indices: A Novel Approach Based on Local Kernel Regression Methods

Abstract: We present a comparative study of computational methods for estimation of ionospheric scintillation indices. First, we review the conventional approaches based on Fourier transformation and low-pass/high-pass frequency filtration. Next, we introduce a novel method based on nonparametric local regression with bias Corrected Akaike Information Criteria (AICC). All methods are then applied to data from the Norwegian Regional Ionospheric Scintillation Network (NRISN), which is shown to be dominated by phase scinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…3(b) and Fig. 4 [7,24]. The local average of Vi was obtained by passing Vi through a 3 rd order Butterworth low-pass filter with a very low cut-off frequency of 0.04 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…3(b) and Fig. 4 [7,24]. The local average of Vi was obtained by passing Vi through a 3 rd order Butterworth low-pass filter with a very low cut-off frequency of 0.04 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…Their computation requires averaging and detrending operations and, in general, algorithms with complex tuning, which are time consuming, computationally expensive, and potentially introduce heavy artifacts, thus altering the scintillation detection process (Mushini et al., 2012). In particular, although detrending the phase by means of a Butterworth filter is the de facto standard (Van Dierendonck, Klobuchar, & Hua, 1993), many authors have shown limitations when dealing with polar scintillations, related to the choice of the filter cutoff frequency, which should be related to the local features of the ionosphere (Forte, 2005; Mushini et al., 2012; Ouassou et al., 2016). A wrong and non‐adaptive cutoff frequency ultimately alters the value of the traditional indices up to the point in which the scintillation detection is completely mistaken.…”
Section: Scintillation Detectionmentioning
confidence: 99%
“…(2012). Alternative scintillation indices, based on non‐parametric local regression with bias Corrected Akaike Information Criteria (AICC) have been proposed by Ouasson et al ., reducing the computational load of wavelet analysis and superior handling of discontinuities (Ouassou et al., 2016). Recently, the Adaptive Local Iterative Filtering (ALIF) method has been proposed to analyse phase time series, improving scale resolution with respect to wavelet transform (Piersanti et al., 2018).…”
Section: Scintillation Detectionmentioning
confidence: 99%
“…This algorithm is different from the standard routines to compute S4, where signal intensity I is used in Equation (1) instead of C/N 0 [21]. However, a benchmarking indicated the effective S4 values computed by Equation (1) are highly correlated with the S4 generated from the NovAtel GPStation-6 receiver, a commercial off-the-shell (COTS) ionospheric TEC and scintillation monitor.…”
Section: Methods and Infrastructurementioning
confidence: 99%